Sampling Size and Auditors' Judgments: A Simulation - Abdul Hamid, Mohamad Ali; Mohamad, Shamsher; Md. Nassir, Annuar (Universiti Putra Malaysia Press, 1996)
Auditors usually seek cost-effective and efficient techniques to accumulate evidence in an effort tu express their opinions on financial statements. One such technique is audit sampling, and in the United Kingdom auditors use sample sizes as small as 25 items. This study uses the Monte Carlo simulation technique to determine whether an auditor's opinion using both different sample size and error levels is within an acceptable degree of accuracy. The results suggest that samples of fewer than 50 items are not large enough to provide a successful sampling plan unless the error value is very low. To improve the sampling plan and the quality of the audit, the sample size should, therefore, be increased to more than 50 items.